2021
DOI: 10.52088/ijesty.v2i1.217
|View full text |Cite
|
Sign up to set email alerts
|

Economic Feasibility Study on The Development of Irrigation Channels

Abstract: Indonesia is an agricultural country where the livelihood of the majority of the population is farming. Geographically, Indonesia is an archipelagic country that has enormous natural potential, both in the marine and agricultural fields. The agricultural sector is a sector that has an important role in improving the welfare of the entire population of Indonesia. Rice fields in Blang Beurandang Village still rely on irrigation from using rainwater to meet irrigation water needs. To increase rice yields, an irri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…The percentage of IRR value given to 12.3% is higher than the bank interest rate which has to be assumed at 8% per year. A higher value of IRR than the yearly interest rate gives effect to more feasible investment to be realized [31]. Regarding the break-even point (BEP) analysis, it is found that the plant will start to make a profit when the minimum capacity limit of the operated plant reaches 36%, which is shown in detail in Figure 13.…”
Section: Resultsmentioning
confidence: 95%
“…The percentage of IRR value given to 12.3% is higher than the bank interest rate which has to be assumed at 8% per year. A higher value of IRR than the yearly interest rate gives effect to more feasible investment to be realized [31]. Regarding the break-even point (BEP) analysis, it is found that the plant will start to make a profit when the minimum capacity limit of the operated plant reaches 36%, which is shown in detail in Figure 13.…”
Section: Resultsmentioning
confidence: 95%
“…Project feasibility analysis can be carried out using the "discounted cash flow" methodology [9], which is the calculation of the growth prospects of an investment in the future which is used in determining the value of NPV, BCR, IRR, and BEP taking into account the interest rate set.…”
Section: Project Feasibilty Analysismentioning
confidence: 99%
“…Desain penelitian yang digunakan adalah kualitatif dan kuantitatif. Desain penelitian kualitatif adalah mencangkup analisa perspektif teknis, manajemen, lingkungan [14], [15] dan pasar [4]. Sedangkan desain penelitian kuantitatif menggunakan perspektif fiansial yang terdiri dari net present value, internal rate of return, payback period dan benefit cost ratio [16], [17].…”
Section: Desain Penelitianunclassified